ASAP CAIR PLUS SEBAGAI PENGGUMPAL LATEKS - Arief Rachmawan; Andi Wijaya (Institut Teknologi Sawit Indonesia, 2017)
As a latex coagulant, liquid smoke has an advantage in reducing putrid odor of rubber coagulum. However, the use ofliquid smoke as latex coagulant requires more doses compared to that o fformic acid, resulting in less efficient process. As much as 1 liter of liquid smoke can be used to coagulate 40 liters of latex only, while 1 liter o fformic acid can be used to coagulate 800 liters oflatex. The idea ofthis research is to combine the advantages of liquid smoke and formic acid to obtain better latex coagulant. The research was done to examine the ability o fAsap Cair Plus (mixture ofliquid smoke andformic acid)asa latex coagulant, and to inform the technical properties of the resulting rubber. The results showed that Asap Cair Plus has an excellent coagulation ability. All technical rubber parameters (Po, PRI, volatile substances and ash content) are as per standard requirements ofthe Indonesian National Standard (SNI) for SIR-20 rubber. As a latex coagulant, the use ofAsap Cair Plus is more cost-effective in terms ofdosage than the use ofpure liquid smoke. As much as 1 liter o fAsap Cair Plus can be used to coagulate 660 liters o ffield latex.